Chapter 1 Introduction (Taylor & Francis, 2021)
This chapter presents an overview of the period of transition in British India which led to the Indianisation of the Civil Services and saw the emergence of Indian administrators who represented India in International forums and led diplomatic missions overseas. It reflects on the strong impressions left by the first Indian prime minister, Jawaharlal Nehru on global affairs and the prominent diplomats who shaped the course of Indian foreign affairs and diplomatic ties with other nations post-independence.